Synthesis, characterization and photocatalytic properties of nanostructured CoFe 2 O 4 recycled from spent Li-ion batteries - Moura, M.N.; Barrada, R.V.; Almeida, J.R.; Moreira, T.F.M.; Schettino, M.A.; Freitas, J.C.C.; Ferreira, S.A.D.; Lelis, M.F.F.; Freitas, M.B.J.G. (Chemosphere (Oxford), 2017)
In this study, cobalt (Co) was recycled from spent lithium ion batteries (LIBs) and used to synthesize cobalt ferrite (CoFe O -LIBs), which was applied as a catalyst for heterogeneous photo Fenton reactions that discolored methylene blue (MB) dye. The co-precipitation method was used to synthesize CoFe O -LIBs and CoFe O -R nanoparticles with spinel structures using as raw materials of the LIB cathodes and commercial reagents. X-ray diffraction (XRD) identified the formation of spinel-type CoFe O , which formed clusters that could be seen under scanning electron microscopy (SEM) analysis and nanometric particles seen under transmission electron microscopy (TEM). Inductively Coupled Plasma Optical Emission Spectrometer (ICP OES) analysis was used to determine the concentrations of metals present in the ferrite, which reached 6.5% (w/w) of Co. The optimal conditions for discoloring the dye were evaluated using a factorial design. Using CoFe O as a catalyst, the best conditions for catalytic reaction were pH 3, 30.0 mg of catalyst, and 8.0 mL of H O 73% (v/v). Discoloration efficiencies of 87.3% and 87.7% were obtained from CoFe O -R and CoFe O -LIBs, respectively. Therefore, CoFe O -LIBs proved to be an efficient catalyst for discoloring MB dye using heterogeneous photo-Fenton reactions. This work is of scientific, social, economic, and environmental interest. It investigates the process of synthesizing,characterizing CoFe O LIBs and the efficiency of degrading MB dye, subjects that have economic and environmental, and therefore, social interest. The work has scientific interest particularly because of the correlation between the structure of the recycled material and its catalytic properties.